Epidemiology and Molecular Typing of Trypanosoma cruzi in Naturally-Infected Hound Dogs and Associated Triatomine Vectors in Texas, USA. - Rachel Curtis-Robles; Karen F Snowden; Brandon Dominguez; Lewis Dinges; Sandy Rodgers; Glennon Mays; Sarah A Hamer (Public Library of Science (PLoS), 2017)
BACKGROUND:Trypanosoma cruzi is the etiologic agent of Chagas disease throughout the Americas. Few population-level studies have examined the epidemiology of canine infection and strain types of T. cruzi that infect canines in the USA. We conducted a cross-sectional study of T. cruzi infection in working hound dogs in south central Texas, including analysis of triatomine vectors collected within kennel environments. METHODOLOGY/PRINCIPLE FINDINGS:Paired IFA and Chagas Stat-Pak serological testing showed an overall seroprevalence of 57.6% (n = 85), with significant variation across kennels. Dog age had a marginally significant effect on seropositivity, with one year of age increase associated with a 19.6% increase in odds of being seropositive (odds ratio 95% CI 0.996-1.435; p = 0.055). PCR analyses of blood revealed 17.4% of dogs harbored parasite DNA in their blood, including both seronegative and seropositive dogs. Molecular screening of organs from opportunistically sampled seropositive dogs revealed parasite DNA in heart, uterus, and mammary tissues. Strain-typing showed parasite discrete typing units (DTU) TcI and TcIV present in dog samples, including a co-occurrence of both DTUs in two individual dogs. Bloodmeal analysis of Triatoma gerstaeckeri and Triatoma sanguisuga insects collected from the kennels revealed exclusively dog DNA. Vector infection with T. cruzi was 80.6% (n = 36), in which T. gerstaeckeri disproportionately harbored TcI (p = 0.045) and T. sanguisuga disproportionately harbored TcIV (p = 0.029). Tracing infection status across dog litters showed some seropositive offspring of seronegative dams, suggesting infection of pups from local triatomine vectors rather than congenital transmission. CONCLUSIONS/SIGNIFICANCE:Canine kennels are high-risk environments for T. cruzi transmission, in which dogs likely serve as the predominant parasite reservoir. Disease and death of working dogs from Chagas disease is associated with unmeasured yet undoubtedly significant financial consequences because working dogs are highly trained and highly valued.